Neutron off-plane scattering of aligned membranes. I. Method Of measurement. - Yang, L (1998)
We describe a method of measuring neutron scattering of aligned membranes with the momentum transfer oriented parallel or partly perpendicular to the plane of the membranes. The method obtains the complete information for the structures within fluid membranes obtainable by scattering. Data from alamethicin- and magainin-induced pores are presented. Although the in-plane scattering curves of these two peptides are similar to each other, their off-plane scattering patterns are strikingly distinct. Magainin pores exhibit intermembrane correlations.